2016
DOI: 10.3390/toxins8100278
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Sporoderm-Broken Spores of Ganderma lucidum on Growth Performance, Antioxidant Capacity and Immune Function of Broiler Chickens Exposed to Low Level of Aflatoxin B1

Abstract: This study was conducted to investigate the toxic effects of aflatoxin B1 (AFB1) and evaluate the effects of sporoderm-broken spores of Ganoderma lucidum (SSGL) in relieving aflatoxicosis in broilers. A total of 300 one-day-old male Arbor Acre broiler chickens were randomly divided into four dietary treatments; the treatment diets were: Control (a basal diet containing normal peanut meal); AFB1 (the basal diet containing AFB1-contaminated peanut meal); SSGL (basal diet with 200 mg/kg of SSGL); AFB1+SSGL (suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 57 publications
6
31
0
Order By: Relevance
“…In the current study, broilers fed diet contaminated with AFB 1 showed a significant decrease in the content of serum IgA, IgG, and IgM when compared with the control group. These results are in consistent with the previous study that showed that AFB 1 is known to be immunosuppressive in birds, and reported that a diet containing AFB 1 significantly reduced the content of serum IgA, IgG, and IgM in broilers [ 48 , 49 ]. These results showed that the humoral function of the body might be impaired by AFB 1 .…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, broilers fed diet contaminated with AFB 1 showed a significant decrease in the content of serum IgA, IgG, and IgM when compared with the control group. These results are in consistent with the previous study that showed that AFB 1 is known to be immunosuppressive in birds, and reported that a diet containing AFB 1 significantly reduced the content of serum IgA, IgG, and IgM in broilers [ 48 , 49 ]. These results showed that the humoral function of the body might be impaired by AFB 1 .…”
Section: Discussionsupporting
confidence: 93%
“…In present study, diet contaminated with AFB1 (350 ppb) induced a significant decrease in body weight of the broilers and adversely effects the overall performance of broiler chickens. Similar detrimental effects reported earlier (Liu et al, 2016) have also been reproduced in the experimental feed of AFB1 in the current study. No mortalities have been recorded in any group during this experimental study.…”
Section: Discussionsupporting
confidence: 92%
“…In current study, the content of LPO was significantly increased in liver of broilers indicating the fact that low level of AFB1 (350 ppb) could enhance the oxidative stress in liver. Similar toxic effects of AFB1 on the oxidative stress were reported in liver of broilers (Liu et al, 2016). Lower oxidative status and higher antioxidant capacity were noticed in broilers fed on a diet supplemented with C. pyrenoidosa.…”
Section: A B C D E Fsupporting
confidence: 78%
“…However, the addition of G. lucidum into the diet significantly eliminated the negative effects of AFB 1 , increased growth performance, and decreased oxidative stress and immune suppression. 83 Chiu et al carried out a study on 42 healthy individuals and divided the participants into two groups. They administrated G. lucidum and placebo (225 mg after lunch and dinner) to the participants and followed them by a six-month interval for one year.…”
Section: Rats Exposed To 4-gy or 8-gy Radiation Dosementioning
confidence: 99%